Looking for Needles in the Plasmodial Haystack - Lars Hviid (American Society for Microbiology, 2019)
ABSTRACT Plasmodium falciparum malaria remains a globally leading infectious disease problem. Despite decades of intense investigation, an efficacious and practical vaccine offering durable protection to people living in areas with transmission of malaria parasites remains an elusive goal. Our fragmentary understanding of the mechanisms of protective immunity to the disease is a major obstacle, and the almost complete focus on a very small subset of P. falciparum proteins as vaccine candidates has left most parasite antigens essentially unexplored as targets of acquired immunity. However, with the protein microarray technology, it is now possible to interrogate the entire parasite proteome for new vaccine candidates and for markers of parasite exposure. Recent mSphere papers describe the results of such research.